1994
DOI: 10.1080/02681219480000561
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical basis for the killing ofCryptococcus neoformansby rat peritoneal cells

Abstract: The biochemical basis of peritoneal cell cytotoxicity for (,'ryptoc~Jccus ne~/brmans was studied by, meast.ring the killing of the yeast by' peritoneal resident cells and peritoneal exudate cells obtained from normal and proteose peptone-rejected animals, respectively. Bolfi cell populations killed ('. ,e~?/brmcm.v to an equivalent extent after 3 h incubation. Exudale cells showed anti-cryptococcal activity from the first hour of" incubation. ~hile no killing was observed with resident cells betk~re 3 h. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…We also observed that following infection there is a change in the behavior of the population in the accessory cells, as reflected by the modification of several functions, such as phagocytosis, lytic activity, and antigen presentation (26). On the other hand, we observed killing of C. neoformans by an NADPH oxidase-dependent mechanism (27). We have recently demonstrated that the proliferative response to mitogens of spleen mononuclear (Spm) cells from C. neoformans-infected rats dramatically decreased in the suppressor period postinfection (28).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…We also observed that following infection there is a change in the behavior of the population in the accessory cells, as reflected by the modification of several functions, such as phagocytosis, lytic activity, and antigen presentation (26). On the other hand, we observed killing of C. neoformans by an NADPH oxidase-dependent mechanism (27). We have recently demonstrated that the proliferative response to mitogens of spleen mononuclear (Spm) cells from C. neoformans-infected rats dramatically decreased in the suppressor period postinfection (28).…”
Section: Introductionmentioning
confidence: 72%
“…Cultures were grown on Sabouraud glucose agar slants at 37°C, maintained by weekly subculture on the same medium, and periodically checked for assimilation pattern, urease production, and virulence. For each infection, yeast cells were harvested from a 3-day culture at 37°C and the precise number of viable cells was determined by triplicate counting of the colony forming units (CFU) on Sabouraud agar after 48 -72 h of incubation at room temperature (27).…”
Section: Microorganismmentioning
confidence: 99%
“…These studies were performed with AM from normal noninfected rats in the absence of exogenous cytokine stimulation and would appear to highlight intrinsic differences between rat and mouse AM. Oxidative killing of C. neoformans is an important mechanism of action for immune effector cells (30,31). Rat AM incubated with catalase and superoxide dismutase showed an increase in cryptococcal lysate fungal burden, suggesting the importance of H 2 O 2 and reactive oxygen intermediates in limiting intracellular growth.…”
Section: Discussionmentioning
confidence: 99%
“…6 Moreover, the NADPH oxidase system was also found to be very important in the mechanism of C. neoformans killing by rat peritoneal cells, with the superoxide anion, hydrogen peroxide (H 2 O 2 ) and the hydroxyl radical being involved in this process. 7 Eosinophils, in contrast, are implicated as effector cells in helminthic infections, releasing their many cytoplasmic granules, containing toxic molecules, in response to antigenic stimuli. 8 Moreover, they notably contribute to allerAna P. Garro, Laura S. Chiapello, José L. Baronetti and Diana T. Masih…”
Section: Both Cd4mentioning
confidence: 99%